Toward creation of a new world history - Haneda, Masashi; Noda, Makito (Tokyo : Japan Publishing Industry Foundation for Culture, 2018)
'Today, as globalization deepens daily and the world becomes increasingly integrated, the time has come to revise the conventional Euro-centric view on world history. The author has been exploring for several years now how best to create a new world history. The world history that we learn and understand today is already out of step with the times. Therefore, it is imperative to envisage a new world history that is suitable to our own time. What description of history, then, is appropriate for our contemporary times? To answer this question, the author first reviews what kind of perception we have of world history and what is wrong with it. Subsequently, he looks into what is the new world history that is called for and how it can be created. The author finds that more and more people are behaving with an awareness of themselves as inhabitants of this earth, willing to mutually transcend differences of views so as to defend this one and only earth of ours and let people the world over live more peacefully and happily. On the basis of these soul-searching explorations, the author comes to propose a world history for inhabitants of the earth from the viewpoint of'there is one world''--
The power of history -- Tracing the history of world history -- Problems with the present world history -- Road to a new world history -- Conceiving a new world history -- Renovation of modern knowledge.
Originally published in Japanese under the title Atarashii sekaishi e by Iwanami Shoten in 2011.
Includes bibliographical references : (pages 196-198).
Colophon also in Japanese.
Keywords: History -- Study and teaching; World history